2019
DOI: 10.2174/1574886314666190612130921
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Abuse Induced Histopathological and Neurobehavioral Disorders in Mice

Abstract: Introduction:Antibiotic abuse is a common phenomenon in Egypt as medications are prescribed without supervision. It is suggested that the excess use of antibiotics modifies the gut microbiota and plays a role in the development of neurological and psychiatric disorders.Objective:The aim of the present study was to use bulb-c mice as models for curam (amoxicillin /clavulanic acid) abuse compared to the locally acting neomycin model, then restoring the probiotic balance to look at the possible effects on the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…The present study aimed to investigate the psychological influence of GM on the central nervous system after the streptomycin treatment of mice. Antibiotics have been used to treat or prevent bacterial infections, but sometimes they cause severe life-threatening side effects that increase the economic burden and mortality of the global population [ 48 , 49 ]. The main problem with antibiotics is that they do not fight against specific harmful bacteria, but instead, kill a variety of other beneficial microorganisms in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to investigate the psychological influence of GM on the central nervous system after the streptomycin treatment of mice. Antibiotics have been used to treat or prevent bacterial infections, but sometimes they cause severe life-threatening side effects that increase the economic burden and mortality of the global population [ 48 , 49 ]. The main problem with antibiotics is that they do not fight against specific harmful bacteria, but instead, kill a variety of other beneficial microorganisms in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance of gut microbiots by antibiotics in an early age tends to alter neurodevelopment which may lead to functional bowel disorders later in life (Caputi et al, 2017). Another study also found that amoxicillin abuse caused gut microbiota dysbiosis and histopathological and neurobehavioral alterations in adult mice, which may explain the rising trend of neuropsychiatric diseases in antibiotics abusing countries (Helaly et al, 2019). Comparing the studies and findings, we find that antibiotic exposure leads to neurotoxicity in fetuses with a low dosage while antibiotic abuse in adults may also induce nerve injury, urging for prudent usage of antibiotics.…”
Section: Antibioticsmentioning
confidence: 96%
“…Apparently, bacteria develop multiple mechanisms of resistance against almost all the available antibiotics (Davies and Davies 2010 ; Munita and Arias 2016 ). The neurotoxic effect result from abuse of antibiotics works by both local and more prominent systemic mechanisms (Helaly et al 2019 ).…”
Section: Antibiotic Abusementioning
confidence: 99%
“…These abnormalities are called dysbiosis and can lead to autoimmune disorders, gastrointestinal disorders, allergies, infections, arthritis, asthma, cancer and obesity (Cardetti et al 2020 ). Abusing antibiotics by taking in excess modifies the gut microbiota and this is studied to be associated with the development of neurological and psychiatric disorders (Helaly et al 2019 ). In a bid to cut down the use of antibiotics amid the controlling of abuse of antibiotics and resistance, antimicrobial peptides (AMPs) in combination with some conventional antibiotics are promising (Liu et al 2020a , b ; Pang et al 2019 ).…”
Section: Antibiotic Abusementioning
confidence: 99%